2010
DOI: 10.1177/1471301210370645
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and faith in dementia

Abstract: This study used a standardized instrument, the Royal Free Interview for Religious and Spiritual Beliefs, to investigate the spirituality of a population of people with dementia who scored 12 or more on the Mini Mental State Examination and their carers, who were attending a West Midlands Memory Clinic. Study patients were more likely to be well preserved cognitively, be female, and to be living with their spouse at home, than the clinic population as a whole. The population was predominantly white British and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 41 publications
(37 reference statements)
0
36
0
Order By: Relevance
“…10 The participants in the 10 studies varied. Four studies used patients, 11,15,25,27 1 used both patients and their caregivers, 28 and another used patients, their families, nurses, and hospital chaplains. 26 The theoretical articles concentrated on methods of delivering spiritual comfort to older adults with dementia by their caregivers 29 and spiritual needs of older adults with dementia.…”
Section: Description Of the Datamentioning
confidence: 99%
See 1 more Smart Citation
“…10 The participants in the 10 studies varied. Four studies used patients, 11,15,25,27 1 used both patients and their caregivers, 28 and another used patients, their families, nurses, and hospital chaplains. 26 The theoretical articles concentrated on methods of delivering spiritual comfort to older adults with dementia by their caregivers 29 and spiritual needs of older adults with dementia.…”
Section: Description Of the Datamentioning
confidence: 99%
“…28 Two studies used mixed methods. The first used observation with pre-and posttests 11 and the second 15 used personal interviews, group interviews, and observation with pre-and posttests.…”
Section: Description Of the Datamentioning
confidence: 99%
“…This left a total of 12 positive psychology outcome measures used within 17 studies for analysis (Table 2). Of the studies included here, three used a combination of self and proxy reporting (Cohen-Mansfeld, Thein, Dakheel-Ali & Marx, 2010;Hilgeman et al, 2014;Jolley et al, 2010). The remainder used selfreport only for the measures included here.…”
Section: Resultsmentioning
confidence: 99%
“…However, testretest reliability was adequate over a one-week period for both philosophical and spiritual subscales (.91 and .95 respectively). Furthermore, construct validity was established as there was a significant relationship between spirituality and the frequency of practice of religious faith (p<.0005) and people with dementia appeared to rate the strength of belief as most important (Jolley, Benbow, Grizzell, Willmott, Bawn, & Kingston, 2010), suggesting additional content validity of the measure.…”
Section: Religiosity/ Spiritualitymentioning
confidence: 99%
“…Notably, there has been little research into the area of religion and dementia and most has been undertaken with people with dementia living in their own homes (for example, Dalby, Sperlinger, & Boddington, 2012;Jolley et al, 2010;Katsuno, 2003;Snyder, 2003). Dalby and colleagues (2012) found that the faith of Downloaded by [University of Nebraska, Lincoln] at 23:03 05 April 2015 people in the early stages of dementia can be a source of comfort and strength that helps them cope with the difficulties of living with dementia.…”
Section: Literature Reviewmentioning
confidence: 97%